Penulisan Kitab Al-Jami’ Al-Azhar fi Hadits An-Nabi Al-Anwar Karya Al-Manawi - Ilyas Daud (Al-Ulum, 2011)
The history of writing and science of hadith have passed a series of very long phase. This paper examines one of the hadith books, i.e. Hadith al-Jami 'al-Azhar Hadith an-Nabi by the Imam Anwar al-Manawi. This paper shows that al-Manawi is an eminent scholar who collected the prophet Muhammad’s tradition in his book al-Jami 'fi al-Azhar al-Hadith al-Nabi al-Anwar and wrote by using various methods and systematical arrangement of traditions based on alphabetical arrangement. This can be seen in indexes (fuhras) book chapters from each book al-Jami fi al-al-hadits al-Anwar of the Prophet. The theme also varied, such as monotheism, worship, morals and law. In this book al Manawi also mentioned about quality of the Prophet’s traditions, both valid hadith, good (hasan) hadith, or false traditions (dhaif).